Cross-sector service use among youth and young adults involved in the Alberta provincial justice system - Cui, Xinjie; Werk, Christine (International Journal of Population Data Science, 2018)
Introduction Youth and young adults who are involved in justice and correctional system often have complex service needs and experience poor health and social outcomes. To improve outcomes for these young Albertans, it is important to understand their characteristics and service utilization patterns across health and social areas. Objectives and Approach The current analysis provides cross-sector service use information on Alberta youth and young adults aged 12 to 25 who were involved in the criminal justice system from 2005 to 2011. Administrative data linked data across multiple Alberta provincial ministries were used for the analysis. These included over 20 programs and services in areas such as health, education, child intervention, disability supports, income support, and justice and corrections. Results Offence types and court outcomes varied by social-demographic characteristics such as age, sex, social economic status, and residential mobility. Elevated mental health and high cost health services use was observed among youth involved in the criminal justice system. Access of social programs such as Child Invention service, Child Support services, Income Support and disability support services was more prevalent among youth and young adults who were involved in the justice system. A higher number of offences was associated with worse education and health outcomes. Conclusion/Implications Cross-sector data linkage and analysis offer a unique opportunity for better understanding of clients/patients and services/programs at the broad system level. Knowledge gained through linked data can inform cross-ministry policies and integration of services.